Modelagem para o c?lculo da perda no percurso de propaga??o em ?reas residenciais nas faixas de VHF e UHF - Escudero, Anderson (2004)
The implementation of digital fixed wireless communication systems, such as digital FM, digital TV (HDTV), WLL (Wireless Local Loop) systems and wireless LANs, require high level of accuracy of propagation prediction in the VHF and UHF bands. This work presents a theoretical model that estimate the average path loss in the propagation between transmission and reception antennas at urban environments, for fixed communications systems. The method is a generalization of the model developed for UHF propagation at urban environments. The modeling presents the average path loss of electromagnetic waves, with good precision for frequencies from 30MHz to 3GHz. The obstacles, in this case the building, are replaced by screens with electromagnetic characteristics. The propagation must occur above and through these structures and the field that crosses each screen are obtained with physical optics approaches. The reflections on the ground are included in calculating the resulting field. Assuming that the signal propagates from a transmission antenna, installed in raised heights, to reception antenna, installed in the average buildings heights, to get the waves incidence angle at the reception point. The representation of the building height variation is gotten with the uniform probability distribution. From the random signal gotten in the simulations, the average strength field is acquired, that normalized give the path loss. Results are obtained for frequency variation, spacing between building and incidence angle of the analyzed signal. The simulations are carried out in MATLAB? platform and the results are in agreement with prediction models and field strength measurements data published in periodicals.